ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH DI WILAYAH SARBAGITA PROVINSI BALI - Krisnayanthi, Putu Arinda; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 8 (2020): VOL 9 NO 8, AGUSTUS 2020 (1631 - 1887), 2020)
Local taxes are contribution to the region, the existence local taxes can help governments to finance development of their respective regions. Sarbagita Region has the highest regional tax revenue among other districts in Province of Bali. Purpose this study to analyze the influence number of tourist visits, population, and gross regional domestic product on regional taxes in the Sarbagita Region of Bali Province partially and simultaneously and analyze the forecast of local tax revenue in the Sarbagita Region of the Province of Bali in 2019 - 2023. Data used is secondary data. Analysis technique used multiple linear regression test. The results showed that simultaneously, the variable number of tourist visits, total population, and gross regional domestic product had a significant effect on local taxes in the Sarbagita Region of the Province of Bali. Partially, the variable number of tourist visits, population, and regional gross domestic product has a positive and significant effect on local taxes in the Sarbagita Region of the Province of Bali. The results of the trend analysis indicate that the forecast of local tax revenue from 2019 to 2023 will continue to increase   Keywords: number of tourist visits, total population, gross regional domestic product, local tax